In Vitro Antiosteoporosis Activity and Hepatotoxicity Evaluation in Zebrafish Larvae of Bark Extracts of Prunus jamasakura Medicinal Plant. (24th September 2020) - Komakech, Richard; Shim, Ki-Shuk; Yim, Nam-Hui; Song, Jun Ho; Yang, Sun Kyu; Choi, Goya; Lee, Jun; Kim, Yong-goo; Omujal, Francis; Agwaya, Moses; Nambatya, Grace Kyeyune; Kan, Hyemin; et al.
Abstract : Osteoporosis is one of the main health problems in the world today characterized by low bone mass and deterioration in bone microarchitecture. In recent years, the use of natural products approach to treat it has been in the increase. In this study, in vitro antiosteoporosis activity and hepatotoxicity of P . jamasakura bark extracts were evaluated. Methods . Mouse bone marrow macrophage (BMM) cells were incubated with tartrate-resistant acid phosphate (TRAP) buffers and p -nitrophenyl phosphate and cultured with different P . jamasakura bark extracts at concentrations of 0, 6.25, 12.5, 25, and 50 μ g/ml in the presence of the receptor activator of nuclear factor kappa-Β ligand (RANKL) for 6 days. The osteoclast TRAP activity and cell viability were measured. Nitric oxide (NO) assay was conducted using murine macrophage-like RAW 264.7 cells treated with P . jamasakura ethanolic and methanolic bark extracts at concentrations of 0, 6.25, 12.5, 25, 50, 100, and 200 μ g/ml. For hepatotoxicity assessment, zebrafish larvae were exposed to P . jamasakura bark extracts, 0.05% dimethyl sulfoxide as a negative control, and 5 μ M tamoxifen as a positive control. The surviving larvae were anesthetized and assessed for hepatocyte apoptosis. Results . TRAP activity was significantly inhibited (p < 0.001) at all concentrations of P . jamasakura extracts compared to the control treatment. At 50 μ g/ml, both ethanolic and methanolic extracts of P . jamasakura exhibited significant (p < 0.01) BMM cell viability compared to the control treatment. P . jamasakura ethanolic and methanolic extracts had significant inhibitory (p < 0.01) effects on lipopolysaccharide (LPS)-induced NO production at 200 μ g/ml and exhibited significant (p < 0.01) and (p < 0.05) stimulative effects, respectively, on RAW 264.7 cell viability. No overt hepatotoxicity was observed in the liver of zebrafish larvae in any of the treatments. Conclusion . The TRAP activity of P . jamasakura bark gives a foundation for further studies to enhance future development of antiosteoporosis drug.